Bibliometric mapping of MCDM methods in AEC industry: identifying trends for sustainable development - Weerakoon, Thilina Ganganath; Turskis, Zenonas; Šliogerienė, Jūratė (Journal of Environmental Engineering and Landscape Management, 2025)
This study investigates integrating multi-criteria decision-making (MCDM) approaches to improve sustainability in the architecture, engineering, and construction (AEC) industry. Through a systemic literature analysis done through the Scopus database and the visualization of key elements through VOSViewer, the study examines the applications of MCDM in sustainable construction, with particular attention to material selection, contractor procurement, waste management, risk assessment, and technological integration, which are essential elements towards sustainable development of the AEC industry. The results highlight how common and successful hybrid MCDM and MADM methods are. These approaches provide all-encompassing answers to challenging problems, from project mitigation to material procurement. The evaluation emphasizes the value of MCDM methods in supporting sustainable practices across the construction lifecycle, streamlining supply chains, and enabling well-informed decision-making. In the end, this study emphasizes how critical it is to carry out further research and apply MCDM frameworks to promote sustainable development in the construction sector and balance development objectives with the protection of the environment and the welfare of society.